Monetary and Structural Determinants of Inflation in Nepal - Shrestha, Pramod Pyara; Timilsina, Sweeta (Nepalese Journal of Economic Studies, 2025)
Inflation is a macroeconomic phenomena that affects the overall performance of the economy. In Nepal, inflation challenges the macroeconomic stability, alarming the need for understanding its determinants and formulating appropriate policies to manage it tactfully. With a high concentration on studies about the demand dynamics of Inflation in Nepal, the study from the supply-side perspective is a pressing need. This study explores the short-run and long-run determinants of inflation in Nepal using both demand-side and supply-side factors. Using the Auto Regressive Distributed Lag Model (ARDL) and Error Correction Model (ECM), the long-run and short-run relationship between Nepalese Inflation and variables: Indian Inflation, Growth in Money Supply, Growth in Agricultural Production, Growth in Petroleum Prices, and GDP Growth Rate is explored. The model is finalized with confidence from the residual and stability tests. Results show the long-run positive relationship of Nepalese inflation with growth in money supply and Indian inflation. Aligning with the inferences, the study finds that the increase in agricultural production has a short-term and significant negative impact on Nepalese inflation.